NOVEL RAHASIA SALINEM KARYA BRILLIANT YOTENEGA DAN WISNU SURYANING ADJI: PERSPEKTIF GASTROCRITICISM - Amalia Tussyahada; Priscila Fitriasih Limbong (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2022)
Indonesia as a culinary paradise has a variety of foods, while literature as a medium can be used as a tool to introduce various Indonesian culinary delights. This study aims to discuss food issues, especially “pecel”, to reveal the secrets of story characters in showing their identity and as an effort to preserve the culinary arts of the Indonesian archipelago. This study uses a qualitative method with a gastro criticism perspective. The research object is the novel Rahasia Salinem by Brilliant Yotenega and Wisnu Suryaning Adji. In this study, food in literature is not only used as the story's object, but both have material, physical, social, and cultural relationships. The results showed four concepts from the perspective of gastro critism, namely (1) food and pleasure, (2) food and art (bricolage), (3) food and names, and (4) food and history. The results of this study are expected to contribute to the development of literary studies in a cultural context as an effort to introduce and preserve local cuisine through literary works.